Simultaneous Determination of the Permeability of a Nafion Membrane to Formic Acid and Water. Issue 6 (16th September 2013) - Dugas, R.; Guay, D.; Tavares, A. C.
Abstract The simultaneous diffusion of formic acid and water through Nafion was measured for four formic acid concentration differentials (1–17.5 M) and for two counter‐ions in the membrane (H+ and Ba2+). An iterative method based on Fick's law is presented to calculate the volumes and concentrations of the solutions as a function of time. Besides the initial conditions, the input parameters are two diffusion coefficients, one of formic acid and one of water, which were adjusted to fit the experimental data. Once the difference in liquid fraction between the two types of membranes is taken into account, the diffusion coefficient of formic acid through Nafion appears independent of the nature of the counter‐ion and the conductivity of the formic acid solution. The diffusion coefficient of water is 10 times higher than the formic acid diffusion coefficient and is systematically lower in membranes in the Ba2+ form than in H+ form.